The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0100-879x2008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Breathing disorders in congestive heart failure: gender, etiology and mortality

Abstract: We investigated the relationship between sleep-disordered breathing (SDB) and Cheyne-Stokes respiration (CSR) while awake as well as mortality. Eighty-nine consecutive outpatients (29 females) with congestive heart failure (CHF; left ventricular ejection fraction, LVEF <45%) were prospectively evaluated. The presence of SDB and of CSR while awake before sleep onset was investigated by polysomnography. SDB prevalence was 81 and 56%, using apnea-hypopnea index cutoffs >5 and >15, respectively. CHF etiologies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…However, after adjusting confounding factors such as age and NYHA functional class, untreated SA (OSA or CSA) has no significant impact on mortality in CHF. These observations were consistent with some previous studies [3][4][5], but conflict with others [6][7][8][9]. After further analyzing these studies, we found that the sample size, study population, end points, statistical tests, etc.…”
supporting
confidence: 90%
“…However, after adjusting confounding factors such as age and NYHA functional class, untreated SA (OSA or CSA) has no significant impact on mortality in CHF. These observations were consistent with some previous studies [3][4][5], but conflict with others [6][7][8][9]. After further analyzing these studies, we found that the sample size, study population, end points, statistical tests, etc.…”
supporting
confidence: 90%
“…It is now recognized that sleep apnea (SA) is very common among patients with congestive heart failure (CHF) [1][2][3][4]. Obstructive and central SA occur in approximately 25% to 37% and 27% to 38% of the CHF patients, respectively [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive and central SA occur in approximately 25% to 37% and 27% to 38% of the CHF patients, respectively [1][2][3][4]. There is also evidence that SA is associated with increased risk of cardiovascular morbidity and mortality in patients with CHF [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies also suggest that daytime PB is associated with a poor prognosis, whereas other studies showed conflicting results [41,44]. Such conflicting results may be explained by the differences of situation and tools used to detect daytime PB across the studies (Table 1).…”
Section: Prognostic Impact and Treatment Optionsmentioning
confidence: 99%
“…One report showed a circadian variation of frequency of PB with three peaks (at 4:00 am, 2:00 pm, and 6:00 pm). PB was less frequently observed in the daytime (approximately one fourth of that in the nighttime) [ [44].…”
Section: Clinical Manifestations and Proposed Pathogenesismentioning
confidence: 99%